Depressive symptoms in elderly women: knowing them to care for - Figueiredo, Maria do Livramento Fortes (Rev Rene, 2017)
The increased life expectancy associated with the improved health conditions has resulted in the increasing and ongoing rise of the elderly population in most societies. Projections show that, by the year 2050, there will be approximately two billion older people across the world, most of who will be living in developing countries. Population aging in Brazil is a phenomenon derived from technological advances in the field of health, particularly the reduced child mortality, the decreased fertility due to the introduction of contraceptive methods, the expanded vaccination coverage and the use of antibiotics and chemotherapy drugs that enabled the prevention and healing of many diseases. Although old age is a universal process, its experience has a great distinction by gender, mainly because there is higher number of elderly women, as aging increases.